Catalytic Domain Plasticity of MKK7 Reveals Structural Mechanisms of Allosteric Activation and Diverse Targeting Opportunities. Issue 10 (15th October 2020) - Schröder, Martin; Tan, Li; Wang, Jinhua; Liang, Yanke; Gray, Nathanael S.; Knapp, Stefan; Chaikuad, Apirat
Summary: MKK7 (MEK7) is a key regulator of the JNK stress signaling pathway and targeting MKK7 has been proposed as a chemotherapeutic strategy. Detailed understanding of the MKK7 structure and factors that affect its activity is therefore of critical importance. Here, we present a comprehensive set of MKK7 crystal structures revealing insights into catalytic domain plasticity and the role of the N-terminal regulatory helix, conserved in all MAP2Ks, mediating kinase activation. Crystal structures harboring this regulatory helix revealed typical structural features of active kinase, providing exclusively a first model of the MAP2K active state. A small-molecule screening campaign yielded multiple scaffolds, including type II irreversible inhibitors a binding mode that has not been reported previously. We also observed an unprecedented allosteric pocket located in the N-terminal lobe for the approved drug ibrutinib. Collectively, our structural and functional data expand and provide alternative targeting strategies for this important MAP2K kinase. Graphical Abstract: Highlights: The N-terminal regulatory helix allosterically stabilizes an active state in MKK7 Diverse covalent type I and type II inhibitors target flexible region in MKK7 Unprecedented discovery of an allosteric binding site for ibrutinib Abstract : Schröder et al. presents a first structure of active MKK7 revealing an allosteric role of the N-terminal helix, providing a model for the MAP2K activation mechanism. Screening identified potent chemically diverse MKK7 inhibitors with diverse binding modes abrogating JNK signaling. Crystal structure revealed ibrutinib binding at an unprecedented allosteric site.